ЗНИЖЕННЯ МІСЦЕВИХ НАГРІВІВ У БАКАХ ПОТУЖНИХ ТРАНСФОРМАТОРІВ ТЕПЛОВІДВІДНИМИ ЛОКАЛЬНИМИ РАДІАТОРАМИ З РЕБЕРНОЮ ОСНОВОЮ - Іванков, В.Ф.; Басова, А.В.; Хімюк, І.В. (Інститут електродинаміки Національної академії наук України, 2021)
The main approaches, the results of numerical modeling, and examples of the practical application of heat-dissipating radiators made of aluminum, with a flat base, and with ribbing to reduce local heating in ferromagnetic covers and walls of transformer tanks, which arise in cases of concentration of magnetic fluxes from multi-ampere taps or magnetic shunts are presented. The case of thermal coupling of a non-magnetic flange of a yoke beam with a flat base of a radiator (copper plate) is considered, which shows the possibility of reducing local heating of the beam using conductive heat transfer between the shelf and the plate and convection heat transfer from their surfaces to cooling oil. References 4, figures 7.